Análise da população de células linfocitárias durante a malária causada por Plasmodium vivax e sua correlação com a parasitemia e a plaquetopenia - Ourives, Samantha Soares (2018)
The mechanisms of activation and regulation of T helper lymphocytes and their cytokines in malaria caused by Plasmodium vivax is complex and poorly understood. Previous data suggest that T helper’s cells balance protective immune responses with immune mediated pathology in malaria. This study investigates the lymphocytic profile of patients infected with P. vivax by identifying and quantifying the specific subpopulations of Th1, Th2, Th17 and Treg cells and observing the correlation between parasitemia and the number of platelets. A cross-sectional study was carried out in an endemic area of the state of Acre, Brazil. In order to obtain identification and quantification of lymphocyte subpopulations through flow cytometry, blood samples were collected from 50 individuals infected with P. vivax and 20 noninfected controls. To differentiate Th1 from Th2, the presence of cytokines IL-4 and TNF-α was examined by enzyme-linked immunosorbent assay (ELISA). The Mann-Whitney and Spearman coefficient tests, comparison and correlation analysis were rendered to test the parasitemia and the number of platelets relationship. The data indicate that individuals infected with P. vivax present a significant reduction in Th1, Th2 and Th17 cell subpopulations when compared to the noninfected control group. A negative correlation exists between parasitemia and platelet counts in individuals infected with P. vivax. There is no correlation of parasitemia or thrombocytopenia with any subpopulation of T lymphocytes analyzed. Patients with serum Th1 cytokine profile presented inversely proportional parasitemia to the increase in the number of Th1, Th2, Th17 and Treg cells while patients with serum Th2 cytokine profile present proportional parasitemia to the increase in number of Th1 and Th2 cells. Regarding the number of platelets, patients with serum Th1 cytokine profile showed a correlation proportional to the Th17 subpopulation. In contrast, platelet counts are directly proportional only to Treg and activated Treg cells in patients with serum Th2 cytokine profile. During the P. vivax infection patients with serum Th1 versus Th2 cytokine profile present different biological mechanisms for activating the immune system against parasite load, leading to different clinical outcomes.